Cyberlaw on pornography - Zulhuda, Sonny (2015)
Internet is the enabling infrastructure of today’s digital society, which sees blurring borders between countries, thus creates an ever dynamic and diverse global community. Just as we start to enjoy this innovative realm called cyberspace, we are confronted by a myriad of questions that challenge the more established values that we have had adopted in “real” space defined by conventional social borders of politics, cultures and religions. One of those challenges lingers around the question of how much we would compromise the cyberspace –our cyberspace– to be the place for harvesting porn and obscenity.